Pengaruh Lingkungan Kerja dan Work Life Balance terhadap Kinerja Melalui Peran Kesehatan Mental (Studi Empiris Karyawan Non Organik di Bank Indonesia Prov. Kep. Bangka Belitung) - Firnandes, Devi; Rizal, Alimuddin (Universitas Syiah Kuala, 2025)
Influencing employee performance improvement through the work environment, work-life balance, and the role of mental health as mediating factors. The population in this study was non-organic employees of Bank Indonesia in the Bangka Belitung Islands Province, with a total of 90 respondents' questionnaire data collected. Respondent data were analyzed using SPSS version 21 software, employing techniques including respondent description, descriptive analysis, instrument validity and reliability testing, and hypothesis testing using multiple regression analysis and mediation analysis. The results of the study show that the work environment does not affect mental health, the work environment has a positive effect on performance, work-life balance has a positive effect on mental health, work-life balance has a positive effect on performance, mental health has a positive effect on performance, and mental health mediates the effect of work-life balance on performance but does not mediate the effect of the work environment on performance. This study has theoretical and managerial implications.